Application of artificial intelligence for the development of academic papers in Peruvian universities: a current problem (Technological Innovations Journal, 2023)
Artificial Intelligence (AI) has unfolded various dimensions since its inception. Its application in academic work has raised concerns in the academic sphere, as improper use by students can pose various risks to their future professional development. The objective was to identify how and how often students from four private universities are utilizing artificial intelligence programs for academic tasks. This was a descriptive, quantitative, non-experimental, and cross-sectional study. The population and sample consisted of students enrolled in research courses at four universities in Peru, totaling 173 students who were surveyed through an online questionnaire. The main findings revealed that 74% of the sample had used some form of AI for academic tasks. A majority of the participants (64,7%) were female, and a significant number were pursuing undergraduate degrees (42,8%) and graduation courses (42,2%). The most notable use of AI was the automation of tasks or academic work (66,4%), and the perceived major benefit of using AI was increased efficiency in content generation (39,8%). A high percentage of university students were found to incorporate AI in their academic work, with primary uses being automation, concept generation, assistance in writing and structuring, and the use of AI as a primary source of information.
Keywords: application; artificial intelligence; jobs; research; university students